2019
DOI: 10.1002/pssr.201900456
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metals in a Cast‐Monocrystalline Silicon Ingot Studied by Silicon Nitride Gettering

Abstract: The concentrations of Cr, Fe, Ni, and Cu in a cast‐monocrystalline silicon ingot grown for solar cell applications are reported. Wafers taken from along the ingot are coated with silicon nitride films and annealed, causing mobile impurities to be gettered to the films. Secondary ion mass spectrometry is applied to measure the metal content in the silicon nitride films. The bulk concentrations of the gettered metals in samples along the ingot are found to be: Cr (3.3 × 1010–3.3 × 1011 cm−3), Fe (3.2 × 1011–2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As mentioned previously, different distributions of Fe in the SiN x films have been observed. While Fe was detected across the entire bulk of the SiN x films in ref , an accumulation of metals (Fe, Cu, Ni, and Cr) at the SiN x /Si interface was observed in refs and . As it is unclear what caused these different impurity distributions, the effective d SiN x is not known.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As mentioned previously, different distributions of Fe in the SiN x films have been observed. While Fe was detected across the entire bulk of the SiN x films in ref , an accumulation of metals (Fe, Cu, Ni, and Cr) at the SiN x /Si interface was observed in refs and . As it is unclear what caused these different impurity distributions, the effective d SiN x is not known.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that silicon nitride (SiN x ) films fabricated by plasma-enhanced chemical vapor-deposition (PECVD), which are commonly used as passivation films and anti-reflection coatings in Si solar cells, can also induce impurity gettering effects at elevated temperatures. In order to estimate the efficiency of the gettering process during cell fabrication and to optimize it, a better understanding of the gettering kinetics and mechanisms must be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in The presence of some of these impurities has been previously reported in the cast-mono wafers. 54 Substitutional C has been shown to be another origin of the formation of low angle grain boundaries, as its concentration well correlates with the etch pit density in castmono wafers. 45 Moreover, Ohno et al 44 and holes (σ p ).…”
Section: Temperature Sensitivity Of Crystallographic Defectsmentioning
confidence: 99%
“…In this work, we conducted a preliminary and comprehensive theoretical calculation of SiN x . At the same time, considering that current classic MD potentials are not suitable for SiN x simulations due to efficiency and accuracy [27][28][29][30][31][32], it is of great interest to train a new potential to describe the interatomic interactions.…”
Section: Introductionmentioning
confidence: 99%